Robust fault detection of nonlinear singular Markov jump systems with partially unknown information - Shi, J.; Yin, YanYan; Liu, Y.; Liu, F. (2017)
© 2017 Technical Committee on Control Theory, CAA. The problem of robust fault detection (RFD) for nonlinear singular Markovian jump systems (NSMJLSs) with partly unknown transition probabilities is investigated in the paper. The RFD observer (RFDO) system and the dynamics of error generator are constructed. By Lyapunov function approach, the proposed method reduces the conservatism compared with the existing ones. Moreover, the performance index is proposed to minimize the influence of the unknown disturbances. Sufficient conditions on the existence of RFDO are established and given in terms of linear matrix inequalities(LMIs). Finally, a simulation example is given to illustrate that the proposed RFDO can detect the faults correctly and shortly after the occurrence.